Chitosan-Based Functional Materials for Skin Wound Repair: Mechanisms and Applications - Feng, Peipei; Luo, Yang; Ke, Chunhai; Qiu, Haofeng; Wang, Wei; Zhu, Yabin; Hou, Ruixia; Xu, Long; Wu, Songze (Frontiers in Bioengineering and Biotechnology, 2021)
Skin wounds not only cause physical pain for patients but are an economic burden for society. With in-depth investigations into the molecular biological mechanisms regarding wound healing and the fast development of tissue engineering biomaterials, a variety of novel biomaterials and hydrogel-like wound care products have become common and functionalized wound dressings in clinical scenarios. Chitosan is a polymeric biomaterial obtained by the deacetylation of chitin. With the properties of easy acquisition, antibacterial and hemostatic activity, and the ability to promote skin regeneration, hydrogel-like functional wound dressings (represented by chitosan and its derivatives) have received extensive attention for their effectiveness and mechanisms in promoting skin wound repair. This article reviewed the mechanisms of chitosan-based functional materials in facilitating skin wound repair and the application of such materials to skin wound treatment.